Pengaruh Pertumbuhan Ekonomi Selama Pandemi Covid-19 Terhadap Tingkat Kemiskinan Di Kabupaten/Kota Provinsi Sumatera Selatan - Andri Irawan; Novegya Ratih Primandari (Ekopem: Jurnal Ekonomi Pembangunan, 2022)
The title of this study The effect of economic growth on poverty levels during the Covid-19 pandemic in the Regency / City of South Sumatra Province. The goal of this study was to see if the declining economic growth rate during the COVID-19 pandemic affected the poverty rate in the South Sumatra Province Regency/City.The hypothesis in this study is that the level of economic growth during the COVID-19 pandemic has a significant influence on the poverty rate in the Regency/City of South Sumatra Province.While the analytical tool used in this study is a simple linear regression analysis of panel data, using secondary data on economic growth rates and poverty rates from 17 districts/cities in the province of South Sumatra between 2019 and 2020. A simple linear regression analysis of panel data revealed that the declining economic growth rate during the COVID-19 pandemic had no significant effect on increasing the poverty rate in the South Sumatra Province Regency/City.The period time used in the study is the study's limitation. The recommendations made to future researchers are related to carrying out research development by incorporating data and other variables. Keywords: Economic Growth, Poverty Rate